2003
DOI: 10.1152/ajplung.00375.2002
|View full text |Cite
|
Sign up to set email alerts
|

Human SP-A 3′-UTR variants mediate differential gene expression in basal levels and in response to dexamethasone

Abstract: Human surfactant protein A (SP-A) is encoded by two genes ( SP-A1, SP-A2), and each is identified with several alleles. SP-A is involved in normal lung function, innate immunity, inflammatory processes, and is regulated by glucocorticoids. We investigated the role of 3′-untranslated region (UTR) of 10 SP-A variants on gene expression using transient transfection of 3′-UTR constructs in the human lung adenocarcinoma cell line NCI-H441. We found: 1) both basal mRNA and protein levels of the reporter gene of SP-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
66
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 64 publications
(93 reference statements)
3
66
0
Order By: Relevance
“…Nucleotide or splice differences within regulatory [5Ј-untranslated region (UTR) and 3Ј-UTR] regions (13,15,32,40,54) have also been observed between the SP-A1 and SP-A2 genes and/or alleles. Quantitative differences include in vitro differences in basal mRNA levels and in response to dexamethasone (26,67) and differences in the SP-A mRNA (17,31) and protein (12,24,58) levels among individuals. The basis for the observed qualitative and quantitative differences may be genetic in nature (15,26,31,40,67).…”
mentioning
confidence: 99%
“…Nucleotide or splice differences within regulatory [5Ј-untranslated region (UTR) and 3Ј-UTR] regions (13,15,32,40,54) have also been observed between the SP-A1 and SP-A2 genes and/or alleles. Quantitative differences include in vitro differences in basal mRNA levels and in response to dexamethasone (26,67) and differences in the SP-A mRNA (17,31) and protein (12,24,58) levels among individuals. The basis for the observed qualitative and quantitative differences may be genetic in nature (15,26,31,40,67).…”
mentioning
confidence: 99%
“…Moreover, qualitative and quantitative differences have been observed in vitro between the SP-A1 and SP-A2 genes (22,36,57,60,(77)(78)(79)(80)(81), pointing to the possibility that the overall functional activity of SP-A may depend on the relative SP-A1-to-SP-A2 levels rather than on the total SP-A content. To address this possibility, it .…”
Section: Discussionmentioning
confidence: 99%
“…Data from in vitro-expressed SP-A1 and SP-A2 variants showed that not only can homooligomers be formed, but these are also functional. In fact, functional (36,57,77) and regulatory (24,39,46,56) differences between SP-A1 and SP-A2 and/or among SP-A variants (78,79) have been observed. Therefore, we deemed it important to assess the SP-A gene-specific protein content in lung health and disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations